Corporate Capture of Blockchain Governance - Ferreira, Daniel; Li, Jin; Nikolowa, Radoslawa (Review of Financial Studies, 2023)
Abstract We develop a theory of blockchain governance. In our model, the proof-of-work system, the most common set of rules for validating transactions in blockchains, creates an industrial ecosystem with specialized suppliers of goods and services. We analyze the interactions between blockchain governance and the market structure of the industries in the blockchain ecosystem. We show that the proof-of-work system may lead to a situation in which some large firms in the blockchain industrial ecosystem—blockchain conglomerates—capture the governance of the blockchain. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.